Open Government: Key Issues of the Open Government Partnership in the Basque Country, Spain - Muslim Afandi; Syed Agung Afandi; Rizki Erdayani (JPW (Jurnal Politik Walisongo), 2025)
This study aims to analyse the main issues of the Open Government Partnership in the Basque Country. The Basque Country plays a leading role in the open government campaign in Spain because it is a pilot program of the local government of the Open Government Partnership. Qualitative approaches and bibliometric analysis methods are used in this study. The research data were obtained from the official website of the Basque Country government and sourced from the Google Scholar database. The findings of this study indicate that the Basque Country's open government is not popular. The key issues in the Basque Country's open government include accessibility, e-government, government websites, transparency, and e-services. Meanwhile, the current issues include public service innovation, private-public partnerships, and autonomy. These issues highlight the urgency and potential contribution of the Basque Country's open government going forward. The Basque Country is currently focusing on its five open government commitments. These commitments contribute to the Basque government's strategic vision by developing tools, models, and common guidelines for all levels of government, thereby increasing the value of public action and the standing of its public institutions and officials. The findings of this study serves as recommendations for stakeholders in the Basque Country, including all local governments in Spain and all members of the Open Government Partnership